The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.7589/0090-3558-48.1.173
|View full text |Cite
|
Sign up to set email alerts
|

Field Immobilization of Molina’s Hog-nosed Skunk (Conepatus chinga) Using Ketamine and Xylazine

Abstract: We injected 27 adult Molina's hog-nosed skunks (Conepatus chinga) intramuscularly by hand with ketamine hydrochloride (KH) and xylazine hydrochloride (XH) in the Pampas grassland of Argentina. Skunks were immobilized with a mean (±SD) dosage of 24.9±6.5 mg/kg KH and 1.9±0.6 mg/kg XH. The mean effective dosages of KH (27.6 mg/kg) and XH (1.7 mg/kg) were higher and lower, respectively, than those reported in skunks previously. Mean induction and recovery time were 5.3±1.9 min and 47.7±18.5 min, respectively. Hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The use of antagonists or reversal agents might facilitate a shorter time to release these animals. However, the prevalence of thermal problems (also reported for other carnivores; Castillo et al , Luengos Vidal et al ) suggests that body temperatures of chemically restrained lesser grisons should be routinely monitored to ensure that efforts to restore the animal to normal body temperature can be initiated promptly.…”
Section: Discussionmentioning
confidence: 99%
“…The use of antagonists or reversal agents might facilitate a shorter time to release these animals. However, the prevalence of thermal problems (also reported for other carnivores; Castillo et al , Luengos Vidal et al ) suggests that body temperatures of chemically restrained lesser grisons should be routinely monitored to ensure that efforts to restore the animal to normal body temperature can be initiated promptly.…”
Section: Discussionmentioning
confidence: 99%
“…Despite an effort was made to maintain normal body temperature during anaesthesia, both animals experienced mild hypothermia at recovery. Similarly, in a recent survey, hypothermia was described as the main complication during field immobilisation of Molina's hog-nosed skunk ( Conepatus chinga ) (Castillo and others 2012). Perianaesthetic hypothermia can cause discomfort at recovery, and is a common complication in small-sized patients owing to the higher basal metabolism and the larger surface-area-to-body-mass ratio compared with larger animals (Farkas 1978).…”
Section: Discussionmentioning
confidence: 86%
“…Although it has been reported that thermal problems are associated with capture procedures (Fowler, 1995;Kreeger et al, 2002;West et al, 2007) and some cases of hypothermia have been reported for carnivores (Spelman et al, 1997;Soto-Azat et al, 2006;Castillo et al, 2012), thermal stress does not appear to be as common in carnivores as in other species (namely ungulates), few detailed descriptions have been published on this topic.…”
Section: Discussionmentioning
confidence: 99%
“…Liberation time (LT) was the interval between injection and complete recovery (normal gait, unimpaired locomotion). Criteria for an ''effective dose'' combination were as follows: (1) mean induction time <11 min (McKenzie, 1993;Kreeger et al, 2002;Castillo et al, 2012), (2) sedation of sufficient depth to allow safe and comfortable handling during at least 15 min, and (3) normal cardiac (90-120 bpm) and respiratory rhythm (20-50 bpm) (Kreeger et al, 1989).…”
Section: Collection Of Datamentioning
confidence: 99%